Präklinische Modelle für Kopf-Hals-Tumoren: Aufklärung zellulärer und molekularer Resistenzmechanismen im Gewebekontext = Preclinical models in head and neck tumors : evaluation of cellular and molecular resistance mechanisms in the tumor microenvironment - Affolter, Annette; Heß, Jochen (HNO, 2016)
Because head and neck squamous cell carcinomas (HNSCC) are characterized by a distinct intertumorigenic and intratumorigenic heterogeneity, they often show substantial differences in the response to established therapy strategies. At present, a multitude of biologics and new pharmacological compounds for targeted therapies are available that allow more efficient and less toxic treatment. There is increasing pressure to establish predictive assays not only for ex ante analysis of the individual patient response to combined chemoradiotherapy and targeted therapies but also for investigation of the efficacy of new drugs. In this respect it is essential to maintain the pathophysiological tissue composition as it is known that paracrine tumor-stroma cell interactions may influence tumor reactivity to treatment. More complex models for individualized sensitivity testing have recently been described and the results are promising to pave the way for personalized cancer therapy. This review article focuses on different systems for maintaining the tumor microenvironment and hence the individual cellular composition, such as 3D organotypic models, organotypic multicellular spheroids, patient-derived xenografts and ex vivo tissue cultures and discusses the advantages and disadvantages in terms of translation into clinical application.